Evaluation of performance for polyurethane injection pile system against lighweight concrete using plaxis / Diana Che Lat - Che Lat, Diana (2013)
Excessive post construction and differential settlements constitute an engineering challenge for structure founded on soft cohesive soil which caused instability and crack to the existing structure. Inadequacy of design for foundation supporting structure during the early stage of construction and less information on site investigation might be the main reason for this problem. Various methods of remedial works have been proposed and implemented for the existing foundation which has been encountered with this settlement problem such as underpinning piles, grouting, pin piles and etc. However, most of these methods require major excavation and disturbance to the existing structure. To overcome this problem, polyurethane (PU) injection pile and slab is proposed to replace the conventional underpinning pile. No excavation is required and only a small diameter hole is drilled on the existing slab foundation before injection of PU. Performance of this method is compared against lightweight concrete slab using finite element analysis called PLAXIS 2D. From analysis that has been carried out, it shows that PU will eliminate the settlements with very minimal disturbance to existing structures, easy and fast installation as well as cost effective long term remedial measures compared to lightweight concrete slab.